Campur Kode Bahasa Pada Peristiwa Jual Beli di Pasar Anyar Kecamatan Bayan - Lestari, Riannitami; Al Pansori, Muh. Jaelani; Mudarman, Mudarman (SENTRI: Jurnal Riset Ilmiah, 2025)
Code-mixing is a common linguistic phenomenon in buying and selling interactions, including those in Anyar Market, Bayan Subdistrict. This study aims to identify the forms of code-mixing and the factors influencing its occurrence in conversations between sellers and buyers in the market. The data collection techniques used were observation, the listening method, note-taking, and documentation. Data analysis employed the Miles and Huberman qualitative model, which includes data reduction, data display, and conclusion drawing. The results show that code-mixing is commonly used, especially by sellers as a communication strategy. The most dominant type is inner code-mixing, which involves the combination of Indonesian and the Sasak language. In addition, outer code-mixing was also found, involving a mix of Sasak with English and Arabic, although in smaller numbers. The forms of code-mixing identified include words, phrases, word repetitions, and clauses. The factors influencing the use of code-mixing include: (1) the interlocutor and the setting of the conversation, (2) habitual language use, (3) the use of popular terms, and (4) the functions and purposes of the communication.